The development of the Francis Moral Values Scales a study among 16- to 18-year-old students taking Religious Studies at A level in the UK - Village, Andrew; Francis, Leslie J. 1947- (2016)
This article reports on the development of scales for measuring moral values in three domains: anti-social behaviour, sex and relationships, and substance use. Students studying religion at A level in 25 schools were invited to respond to 32 Likert items that referred to a wide range of moral issues and behaviours, employing a 5-point response scale. In the first study, responses from 652 students were subject to an exploratory factor analysis, which identified three factors that explained 47% of the variance. Three summated scales were produced that had very good internal consistency reliability: the anti-social behaviour scale (seven items, Cronbach's α = .83), the sex and relationships scale (seven items, α = .84), and the substance use scale (five items, α = .87). In the second study, a repeat survey among the same schools a year later resulted in a second sample of 462 students. Confirmatory factor analysis indicated that the 19 items identified in the first study could be satisfactorily fitted to a model with the same three latent constructs. These constructs are recommended as a parsimonious way of assessing general moral values among adolescents.
Keywords: Religion; Students; moral values; Psychometrics